The Influence of Technology on International Environmental Law and Its Implications For Indonesian Environmental Law - Gratius Domini Serang; Joko Setiyono (Journal of Social Research, 2025)
Technology itself is a human creation that was created with the aim of making it easier and helping humans in this case solve a fundamental problem in society. However, the development of technology is also not free from negative impacts. The birth of law to control air pollution resulting from the use of coal was clearly visible when the British government took steps to create "The Smoke Abatement Act". ecosystem. In international law itself, rules regarding the use of technology have been implemented, where this law was born out of human awareness of the magnitude of the impact of changes in the environment due to technology.